Effects of Ticlopidine of Platelet Function in Men with Stable Angina Pectoris - Berglund, Ulf; Schenck, Henning von; Wallentin, Lars (Thrombosis and Haemostasis, 1985)
The effects of ticlopidine (T) (500 mg daily) on platelet function were investigated in a double-blind placebo-controlled study in 38 middle-aged men with stable incapacitating angina pectoris. The in vitro platelet reactivity to aggregating agents, the platelet sensitivity to prostacyclin and the plasma levels of platelet specific proteins and fibrinogen were determined before and after 4 and 8 weeks of treatment. T exerted a potent inhibitory effect on ADP- and collagen-induced platelet aggregation. The effect of T was proportional to the pretreatment reactivity to ADP and collagen. The inhibitory effect of T on the epinephrine response was less pronounced. The plasma levels of beta-thromboglobulin, platelet factor 4 and fibrinogen were not influenced by T. The platelet inhibition of prostacyclin was potentiated by T, and it was demonstrated that T and prostacyclin had synergistic inhibitory effects on platelet aggregation.
Keywords: Ticlopidine; Platelet function; Angina pectoris; Prostacyclin